A comprehensive review of international students' perceptions of the learning environment in relation to academic achievement - Masud, Nuruddin Ahmed; Mensah, Joshua; San, San Su Su; Subarna, Mst Taherun Nesa; Hasan, Mahmudul (Journal of Social, Humanity, and Education, 2023)
Purpose: The primary purpose of the research is to pursue the international student's perception of the learning environment related to academic achievement in international universities to establish the elements of an educational culture that contribute to the academic achievement of international students. Research methodology: Numerous studies have been conducted over the last few decades to determine how students perceive their learning environment as reflected by their average level of academic achievement. The impact of international students from the Asian & African continent and their social, cultural, and educational experiences on their academic achievement was evaluated by reviewing global and local materials conducted at one Chinese university in Zhejiang province. This study commenced with a search of computerized educational, sociology, and psychology databases using the exploratory phase method. The materials for the review are divided into two sections: a synopsis of academic, social, and cultural consequences & a description and criticism of strategies for promoting international competitiveness and fostering intercultural understanding. Results: International students' perception of the learning environment has a significant impact on academic achievement at international foreign universities, and the findings of this study stimulate the researcher to emerge with new strategies that can heighten the performance of international students.